(x – 2)^2 Please explain how to expand.
Last edited by mr fantastic; Nov 26th 2008 at 02:10 PM. Reason: Clarifification provided by the OP
Follow Math Help Forum on Facebook and Google+
Originally Posted by Elli (x – 2)^2 $\displaystyle (x-2)^2 = (x-2)(x-2) = x^2-2x-2x+4 = x^2-4x+4 $ make two brackets then foil.
Originally Posted by Elli (x – 2)^2 Please explain how to expand. hi it is like (a-b)^2 ^-whole square (a-b)^2=a^2-2ab+b^2 (^power2) (x-2)^2=x^2-2*x*2+2^2 (x-2)^2=x^2-4x+4 ok
Last edited by mr fantastic; Nov 26th 2008 at 02:12 PM. Reason: Edited quote to match edit of original post
I would learn to use saranya's method ASAP. Saves you a ton of time on tests and on future problems.
Thank you for your help .. euclid2, petergunz and saranya
View Tag Cloud